In vivo study on murine species using Cytarabine magnetic microspheres - Satinder Kakar; Anurekha Jain; Ramandeep Singh (International Journal of Public Health Science (IJPHS), 2020)
Cytarabine magnetic microspheres were formulated and checked for their antileukemic potential. Leukemia was persuaded in the Wister strain of rat by intravenous injection of benzene. Blood was procured and various hematological parameters were noted and compared. Animals were divided into four groups, antileukemial potential was found to be maximum in case of magnetic microspheres of Cytarabine. The study shows the Antileukemic potential of Cytarabine magnetic microspheres.